2008
DOI: 10.1111/j.1755-5922.2008.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Profile of the Selective Mitochondrial F1F0 ATP Hydrolase Inhibitor BMS‐199264 in Myocardial Ischemia

Abstract: The mitochondrial F 1 F 0 ATP synthase is responsible for the majority of ATP production in mammals and does this through a rotary catalytic mechanism. Studies show that the F 1 F 0 ATP synthase can switch to an ATP hydrolase, and this occurs under conditions seen during myocardial ischemia. This ATP hydrolysis causes wasting of ATP that does not produce work. The degree of ATP inefficiently hydrolyzed during ischemia may be as high as 50-90% of the total. A naturally occurring, reversible inhibitor (IF-1) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 51 publications
1
36
0
Order By: Relevance
“…86) The complex regulation of HF o F 1 has been shown to be essential for daily human activity that is triggered by the brain (Fig. 10), thus human bioenergetics is also applicable to emergency medicine 113,118) and obesity/diabetes 23,116) and mitochondrial diseases. 87,97) …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…86) The complex regulation of HF o F 1 has been shown to be essential for daily human activity that is triggered by the brain (Fig. 10), thus human bioenergetics is also applicable to emergency medicine 113,118) and obesity/diabetes 23,116) and mitochondrial diseases. 87,97) …”
Section: Discussionmentioning
confidence: 99%
“…BMS-199264 selectively inhibits ATPase activity during ischemia while having no effect on ATP synthesis, and enhances the recovery of contractile function following reperfusion. 118) IF 1 , ectopic HF o F 1 and the opener of mitochondrial ATP-sensitive K + channel 113) protect cardiomyocytes from ischemic/reperfusion damage.…”
Section: In Vivo Atp Synthesis: Fof1 In Human Bioenergetics and Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Excessive ATP hydrolysis decreases the cardiac energy reserve leading to HF (151). Grover et al reported selective F 1 F 0 -ATPase inhibitor BMS-199264 with significant cardio-protective profile by reducing ATP hydrolysis (152). Thus, the F 1 F 0 -ATPase can be a target for nanotechnology-based tools against HF and IR.…”
Section: Mitochondrial Targets For Cardiovascular Diseases (Cvd)mentioning
confidence: 99%